The Effect of Current Ratio (CR), Debt Equity Ratio (DER), Total Asset Turnover (TATO) on Return of Equity (ROE) in the Manufacturing Industry of Consumer Goods Sector in 2019-2021 - Arista Widya; Suaibatul Aslamiyah (Universitas Muhammadiyah Gresik, 2023)
Manufacturing companies are the main pillar of industrial development in a country. The development of the manufacturing industry in a country can also be used to see national industrial development in that country. This development can be seen both from the aspect of the quality of the products produced and the performance of the industry as a whole. The manufacturing sector made the largest contribution to the increase in Indonesia's economic growth which reached 7.07% in the second quarter of 2021. This sector was the highest source of growth, namely 1.35%. The manufacturing sector itself recorded growth of 6.91% despite being under pressure. due to the Covid-19 pandemic. This study aims to examine the effect of the variables Current Ratio (CR), Debt Equity Ratio (DER), Total Asset Turnover (TATO) on Return Of Equity (ROE). The sampling technique used is panel data with the criteria for manufacturing companies in the consumer goods sector that publish financial reports (annual reports) for the 2019-2021 period. Obtained a total sample of 36 companies with a period of 3 years to obtain 108 data. The analysis technique used is multiple linear regression analysis equipped with normality, multicollinearity, autocorrelation, and heteroscedasticity tests to obtain an unbiased estimation model. The hypothesis was tested using the t-statistic to test the significance of the regression coefficient partially at a significance level of 5%. The results of this study indicate that the Current Ratio (CR) has a positive and significant effect on Return Of Equity (ROE) with a sig = 0.027 <0.05, Debt To Equity Ratio (DER), has a positive and significant effect on Return Of Equity (ROE) with a sig = 0.014 <0.05, Total Asset Turnover (TATO) has a positive and not significant effect on Return Of Equity (ROE) with a sig = 0.147 > 0.05.